MOTIVASI IBU NIFAS DALAM PEMBERIAN ASI EKSKLUSIF MENGGUNAKAN MOTIVATION FOR HEALTH BEHAVIOR SCALE (MHBS) - Rochmawati, Rochmawati (Jurnal Kebidanan, 2025)
This study aims to measure the motivation level of postpartum mothers in exclusive breastfeeding using the Motivation For Health Behavior Scale (MHBS), analyze the relationship between sociodemographic factors and motivation, and assess the relationship between motivation level and the sustainability of exclusive breastfeeding. A cross-sectional research design was used involving 228 postpartum mothers in Tangerang City and Regency selected through purposive sampling. Data collection utilized the MHBS instrument consisting of three dimensions: autonomous motivation, controlled motivation, and amotivation. The results showed that the majority of respondents (58.3%) had high motivation levels, with 65.8% having high autonomous motivation. Statistical analysis revealed significant relationships between education level and autonomous motivation (p=0.003), employment status and controlled motivation (p=0.021), and family support with all three motivation dimensions (p<0.05). Autonomous motivation had the strongest relationship with exclusive breastfeeding sustainability (OR=5.23; 95% CI: 3.12-8.75), followed by controlled motivation (OR=1.87; 95% CI: 1.09-3.21), while amotivation was negatively associated with exclusive breastfeeding (OR=0.31; 95% CI: 0.17-0.58). Mothers with high motivation were 4.18 times more likely to consistently provide exclusive breastfeeding. In conclusion, the motivation of postpartum mothers, especially autonomous motivation, plays an important role in the sustainability of exclusive breastfeeding. Interventions focusing on strengthening autonomous motivation through improved education and family support are needed to increase exclusive breastfeeding coverage. The use of MHBS as a motivation measurement instrument provides a more comprehensive approach in identifying determinants of exclusive breastfeeding.